Analisis Kepuasan Pengguna Aplikasi Nyari Gawe Menggunakan Model Technology Acceptance Model (TAM) dan K-Means Clustering - Syahrul Anwar (Jurnal Sosial Teknologi, 2026)
Construction projects in DIY have high complexity because they are located in disaster-prone areas such as earthquakes, floods, and landslides, so they require structured risk management. This research aims to analyze the influence of cost, quality, time, and accident risk identification on disaster risk management of construction projects. The research employed a quantitative approach by distributing questionnaires to 30 respondents consist of contractors, consultants, and project supervisors. Data were analyzed using statistical test multiple linear regression to examine the influence of each aspect on disaster risk management. The findings indicate that cost risk identification has a significant effect on risk management effectiveness, particularly in preventing budget overruns caused by external conditions such as material inflation and supply uncertainty. The quality aspect contributes substantially to improving construction resilience against disasters, in line with the application of quality standards based on SNI and ISO. The time aspect shows a clear influence on successful risk mitigation, as project delays increase vulnerability to disaster impacts. Meanwhile, accident risk identification is strongly related to the contractors’ readiness in implementing occupational health and safety (OHS) procedures to reduce potential human and material losses. Overall, this study emphasizes the importance of integrating risk identification into the construction project management system in the Special Region of Yogyakarta Province. The findings provide practical implications for contractors, local governments, and other stakeholders in developing adaptive, measurable, and responsive risk management strategies in disaster-prone regions.